Implantation in the lower half of the uterine cavity and decreased trophoblastic thickness can predict subsequent miscarriage: a prospective cohort study - Lewis Nancarrow; Nicola Tempest; Suganthi Vinayagam; Steven Lane; Andrew J Drakeley; Roy Homburg; Richard Russell; Dharani K Hapangama (Bioscientifica, 2023)
Embryo implantation is vital for successful conception but remains to be fully understood. Trophoblast invasion is key for implantation, with anchorage and depth of placentation determined by its extent. There is a dearth of synchronous information regarding IVF, implantation site, and trophoblastic thickness (TT). Our aim was to determine whether pregnancy implantation site and TT, had an impact on outcomes of IVF pregnancies. This prospective observational study was undertaken at a tertiary referral UK fertility unit over 14 months, collecting data on implantation site and TT from three-dimensional (3D) images of the uterus following early pregnancy scan. Of the 300 women recruited, 277 (92%) had live births, 20 (7%) miscarried, 2 (0.7%) had stillbirths, and 1 (0.3%) had a termination. Significantly more pregnancies that resulted in miscarriage (7/20, 35%) were located in the lower uterine cavity when compared to ongoing pregnancies (15/277, 5%) (P < 0.01). TT was significantly higher in ongoing pregnancies when compared with those who miscarried (7.2 mm vs 5.5 mm; P < 0.01). Implantation in the lower half of the uterine cavity and decreased TT are significantly associated with an increased rate of miscarriage. Identification of those at risk should prompt increased monitoring with the aim of supporting these pregnancies.